Constitutional legal support of the modern Russia’s state unity and territorial integrity (socio‐economic aspect) - Svyatoslav V. Ivanov (Правоприменение, 2019)
The subject. The article is devoted to the analysis of the socio‐economic aspect of public authorities’ activities with regard to constitutional legal support of the state unity and territorial integrity of the Russian Federation.The purpose of the article is to confirm or refute the hypothesis on the shortage of constitutional regulation of socio‐economic policy of modern Russia in the context of ensuring its state unity and territorial integrity.The methodological basis of the study includes general‐scientific methods (analysis and synthesis, system‐structural approach) as well as academic methods (formal‐legal method, method of interpretation of legal acts).Results, scope. The socio‐economic aspect of the constitutional legal support of state unity and territorial integrity of Russia implies consistent provision of a decent standard of living throughout the country, as well as strengthening economic ties between the subjects of the Russian Federation as one of the key factors in preserving the territorial integrity of Russia. In this regard, the constitutional legal support of the unity of the economic space of the Russian Federation, the alignment of the level of socio‐economic development of the subjects of the Russian Federation are of particular importance.Conclusions. The consistent implementation of the constitutional legal guarantees is accompanied by a number of problems identified in the law enforcement practice of the Federal bodies of state power. It seems that it is necessary to expand the range of entities entitled to initiate the procedure of dismissal of the Chairman of the Central Bank of the Russian Federation. It is required in the long term to consolidate the principle of alignment of socio‐economic development of subjects of the Russian Federation among the foundations of the constitutional system. Finally, it seems that there is a need for a more thorough constitutional settlement of the General principles of taxation and fees, budget regulation in Russia.